Disorder-Specific Psychodrama Therapy in Theory and Practice - Krüger, Reinhard T. (Psychodrama in Counselling, Coaching and Education, 2024)
The open access book explains the practical approach in psychodrama with the help of multidisciplinary theories of self-development, mentalization, play, and psychosomatic resonance. These theories help to structure the therapeutic experiences of Moreno and other psychodramatists and to compare them with experiences and theories of other psychotherapy methods. Against this background, the author develops models of a disorder-specific psychodrama therapy for people with personality disorders, borderline organization, trauma disorders, anxiety disorders, obsessive-compulsive disorders, depression, grief reactions, suicidal crises, masochism, psychoses, addiction disorders, eating disorders, and behavioral addictions. The therapy models convey a deep understanding of these disorders and sometimes open up new ways of treatment. They can be used both in individual and in group therapy. The methods are explained with the help of more than 120 case examples. The theoretical explanation makes the psychodramatic action methods accessible and applicable to therapists from other schools of therapy as well as in counseling and coaching. This makes the practical work therapeutically more effective and creative. This is an open access book.